Partial fraction decompositions and further trigonometric identities - Wang, Xin; Zheng, De-Yin (Utilitas Mathematica, 2008)
Partial fraction decomposition method is employed to investigate trigonometric sums over the angles equally distributed on the upper half plane. Generating functions and explicit formulae are derived by means of formal power series technique.